Relative Bioavailability of Sotorasib Following Administration as a Water Dispersion to Healthy Subjects and Compatibility With Enteral Administration - Cardona, Panli; Spring, Marintan; Bao, Jiemin; Xie, Yong; Houk, Brett (Clinical pharmacology in drug development, 2025)
Sotorasib is approved to be taken as 960 mg orally once daily (8 × 120-mg tablets) for the treatment of KRAS G12C-mutated nonsmall cell lung cancer. Dispersion of tablets in water could be an alternative method for patients who require a liquid formulation due to dysphagia and enteral administration. A clinical study was conducted to assess the pharmacokinetics of 960 mg of sotorasib administered as tablets and as tablets dispersed in water in healthy volunteers. Each subject received 960 mg of sotorasib by mouth, as tablets and as tablets dispersed in water on Days 1 and 4. Sotorasib median time to maximum observed plasma concentration was similar when administered as tablets and as tablets predispersed in water. The geometric least squares mean ratios (water dispersion/tablets) for area under the concentration-time curve from time 0 extrapolated to infinity and maximum observed plasma concentration were 1.049 and 1.080, respectively. Sotorasib 960 mg was well tolerated. Administration of 960 mg of sotorasib as tablets predispersed in water achieved similar systemic exposures to that of sotorasib administered as oral tablets. In vitro evaluations were performed to assess the feasibility of administering sotorasib through an enteral feeding tube. Approximately 98% of sotorasib was recovered, with no new impurities, from enteral feeding tubes. Collectively, these results support that sotorasib can be administered by mouth and via enteral feeding tubes as tablets predispersed in water.